Hedging catches on - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
In the April 2002 issue of Spore (98), the article 'The dice have no dots' made a strong plea for producers to consider taking out insurance against calamities, as protection against low yields or rock-bottom prices for their commodities. A novel...